Photochemical reactivity of PLA at the vicinity of glass transition temperature. The photo-rheology method. (August 2016) - Marek, Adam A.; Verney, Vincent
Graphical abstract: Highlights: An influence of chain mobility onto the photochemical reactivity of PLA is exemplified. The photochemical reactivity of PLA close to the glass transition region was determined. The differences in the rheological behaviour were measured using photo-rheology method. The intensity of photochemical reactivity corresponds to thermal data from DSC. Abstract: A photo-rheology method was applied to determine photochemical reactivity of poly(lactic acid) close to glass transition region. The differences in the rheological behaviour were measured during in situ UV irradiation in air. At low frequency (1 rad s −1 ), the highest reactivity was observed at the glass transition temperature which corresponds to the data from DSC. Below and above this temperature, the rate of PLA chain scission degradation was lower. Moreover, it was also shown that changing the oscillation frequency led to the maximal rate of the chain scission rate occurring at temperatures slightly higher (shifted due to time-temperature superposition effects).